Increased chronic lymphocytic leukemia proliferation upon IgM stimulation is sustained by the upregulation of miR‐132 and miR‐212. Issue 4 (2nd February 2015) - Tavolaro, Simona; Colombo, Teresa; Chiaretti, Sabina; Peragine, Nadia; Fulci, Valerio; Ricciardi, Maria R.; Messina, Monica; Bonina, Silvia; Brugnoletti, Fulvia; Marinelli, Marilisa; Di Maio, Valeria; Mauro, Francesca R.; et al.
<x xml:space="preserve">Abstract</x> To assess the involvement of microRNAs (miRNAs) in B‐cell receptor (BCR) stimulation, we first evaluated miRNA profiling following IgM cross‐linking in chronic lymphocytic leukemia (CLL) cells and in normal B lymphocytes. Second, we combined miRNA and gene expression data to identify putative miRNA functional networks. miRNA profiling showed distinctive patterns of regulation after stimulation in leukemic versus normal B lymphocytes and identified a differential responsiveness to BCR engagement in CLL subgroups according to the immunoglobulin heavy chain variable region mutational status and clinical outcome. The most significantly modulated miRNAs in stimulated CLL are miR‐132 and miR‐212. Notably, these miRNAs appeared regulated in progressive but not in stable CLL. Accordingly, gene profiling showed a significant transcriptional response to stimulation exclusively in progressive CLL. Based on these findings, we combined miRNA and gene expression data to investigate miR‐132 and miR‐212 candidate interactions in this CLL subgroup. Correlation analysis pointed to a link between these miRNAs and RB/E2F and TP53 cascades with proproliferative effects, as corroborated by functional analyses. Finally, basal levels of miR‐132 and miR‐212 were measured in an independent cohort of 20 unstimulated CLL cases and both showed lower expression in progressive compared to stable patients, suggesting an association between the expression of these molecules and disease prognosis. Overall, our results support a model involving miR‐132 and miR‐212 upregulation in sustaining disease progression in CLL. These miRNAs may therefore provide new valuable strategies for therapeutic intervention. © 2015 Wiley Periodicals, Inc.